Health Education on Parents' Attitudes in Handling Early Seizures of Fever in Children in the Children's Room of Toto Kabila Hospital - Nur Fadila Manti; Herlina Jusuf; Ibrahim Suleman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Fever spasms are one of the emergency conditions that often occur in children and can cause anxiety in parents. Parents' attitudes play a very important role in providing early treatment of febrile seizures and preventing complications in children. The purpose of the study was to determine the influence of health education on the attitude of parents in the early treatment of febrile seizures in children in the children's room of Toto Kabila Hospital. The type of quantitative research uses a pre experiment design with one group pre test-post test. The sampling technique used non-probability sampling with a purposive sampling approach. The study population was parents who had children aged 1-5 years in the Children's Room of Toto Kabila Hospital as many as 96 people, and a sample of 49 respondents. Data analysis was conducted using the Wilcoxon Sign Rank Test. The results showed that there was a significant difference between the pretest and posttest scores with (p-value = 0.000 < ? = 0.05). In conclusion, there is an influence of health education on the attitude of parents in the early handling of febrile seizures in children in the Children's Room of Toto Kabila Hospital. For health workers, it is expected to develop a routine health education program or brief counseling for each service related to signs/symptoms and early treatment of febrile seizures.